-2(x-3)=3(1+2x)

Simple and best practice solution for -2(x-3)=3(1+2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-3)=3(1+2x) equation:



-2(x-3)=3(1+2x)
We move all terms to the left:
-2(x-3)-(3(1+2x))=0
We add all the numbers together, and all the variables
-2(x-3)-(3(2x+1))=0
We multiply parentheses
-2x-(3(2x+1))+6=0
We calculate terms in parentheses: -(3(2x+1)), so:
3(2x+1)
We multiply parentheses
6x+3
Back to the equation:
-(6x+3)
We get rid of parentheses
-2x-6x-3+6=0
We add all the numbers together, and all the variables
-8x+3=0
We move all terms containing x to the left, all other terms to the right
-8x=-3
x=-3/-8
x=3/8

See similar equations:

| x+6=9+3x | | 7x=70−3x | | 4*x+4=20 | | 4^4-5x^2+7=0 | | 6=1x/5 | | x–5=4 | | 8=17-q | | 4+3a=10 | | c/5-5=2 | | 6+c/9=15 | | 2-4a=2+4a | | 8x-25=7x-5 | | x-23=2x+29 | | 12x=18x-9 | | 0.2x-0.66(30)=15 | | 1500-x=0.2x | | m-2/3+1=1m/7 | | 1/5x-2/3(30)=30 | | 5(x-1)+4=39 | | X=(38-x)+18 | | 6g+13+2g=45 | | X^2+30*x-117=0 | | 10x+5=5¥ | | 2.5-2=3-x | | 3-2.5=2-x | | 5(5x+7)+8=-32 | | 3-2=2.5-x | | 5(p-6)+7=2 | | 5(2m-5)=55 | | 8x-3=6+11x | | 3x-7+15x-1=150 | | (X+2)²-4x=8 |

Equations solver categories